Total 36 tooth reinclusion in a 7-year old patient - Bąk, Tomasz; Bal, Wioletta; Topyła, Weronika; Krasuska, Beata; Gawęda, Anna; Wojciechowicz, Jolanta; Tomaszewski, Tomasz (Journal of Education, Health and Sport, 2018)
The phenomenon of permanent teeth reinclusion is an extremely rare occurrence both in clinical cases of patients and in literature descriptions. Untreated process may lead to many pathological consequences, such as: formation of abscesses, fistulas or, as in the case of the patient described, perforation of the buccal’s bone plate covering the 36 tooth. The article describes a very rare case of complete reinclusion of tooth 36 in a 7-year-old patient. Taking into account the risk of surgical complications, it was decided to perform the procedure in a hospital’s conditions.